Pemanfaatan Teknologi dalam Pengelolaan Minyak Jelantah Serta Dampaknya Bagi Perekonomian Warga Lokal Studi Kasus: Bank Sampah Ngudi Lestari, Kota Semarang - Saraswati, Padmagitaning; Susilowati , Indah; Kusumawardhani, Hapsari Ayu; Lestari , Esti; Simangunsong, Cindy Dwi Septiana; Sakina , Masita; Arinda Thira Novia Setiawan (Jurnal Pengendalian Pencemaran Lingkungan (JPPL), 2025)
Every household produces used cooking oil as waste that has no economic value. Some people still dispose of used cooking oil into water channels and soil, due to a lack of insight into the impact of this behavior on the environment. The Ngudi Lestari Waste Bank in Tinjomoyo Village became an educational place for the community to understand the importance of managing used cooking oil and providing economic opportunities for the community. This study aims to identify the characteristics of used cooking oil management at the Ngudi Lestari Waste Bank, describe the use of technology in the process of managing used cooking oil and wax at the Ngudi Lestari Waste Bank, analyze the economic value of used cooking oil management and strategies that can be developed to expand the network and use of technology in the management of used cooking oil at the Ngudi Lestari Waste Bank. The analysis was carried out using the recognition survey method, descriptive analysis, cost and return, transaction cost, and triangulation. It was found that they do not use any technology from the collection to the marketing stages in the Ngudi Lestari Waste Bank system. Strategies such the use of online questionnaires, collaborating with third parties, using e-commerce platforms to utilizing social media in marketing aspects can be used. Overall, the management of used cooking oil at the Ngudi Lestari Waste Bank not only contributes to the environment but also provides economic benefits to improve the economy of local residents. Keywords: management, strategy, used cooking oil, utilization of technology, waste bank